Genetic variability, character association and path coefficient analysis in orchids (Orchid spp) of Mizoram, Sikkim and Darjeeling District of West Bengal for various quantitative traits - VANLALRUATI, VANLALRUATI; MANDAL, T; PRADHAN, S (The Indian Journal of Agricultural Sciences, 2016)
Efforts were made on augmentation of orchids germplasm in different parts of Mizoram, Pakyong (Sikkim) and Pedong (Darjeeling hills of West Bengal) during 2011-2013 to estimate the genetic variability, heritability, genetic advance, correlation and path coefficient in seventy nine diverse genotypes of orchids on 14 important quantitative traits. Germplasms were evaluated for various vegetative, floral and spike quality related traits. Flower quality characters like length of spike, length of internode of the spike, length of pedicel were found to be high in the species like Arundina graminifolia and Cymbidium aloifolium. However, the number of florets/spike was more in Oberonia orbicularis and Oberonbia iridifolia and Phaius tankervillae recorded biggest floret size. Spike longevity was found to be high in Dendrobium formosum and Vanda parishii. Spike yield was maximum in Dendrobium chrysanthum and Dendrobium eriaeflorum. The study revealed wide variation for all the characters indicating sufficient genetic variability to be exploited in breeding programme. The maximum value of PCV and GCV was recorded for floret diameter. High heritability coupled with high genetic advance was observed for plant height, leaves/pseudobulb, florets/spike, floret diameter and pedicel length. Selection on the basis of these characters would be more effective for the improvement of orchids. Spike length showed positive and highly significant association with spike longevity and number of florets/spike at genotypic and phenotypic level. Highly significant correlation of spike yield was found with pseudobulbs/plant, leaf dimensions, flowers/spike and number of spike/pseudobulb at both the levels of correlation coefficient.